Synthesis and properties of biodegradable polylactide and thermoplastic starch blends - Świerz-Motysia, B.; Jeziórska, R.; Szadkowska, A.; Piotrowska, M. (Polimery, 2011)
The results of studies of the influence of a compatibilizer on the properties of binary polylactide (PLA) and thermoplastic starch (TPS) blends have been presented. The polylactide modified with reactive anhydride groups (PLAm) was applied as compatibilizer. The synthesis of thermoplastic potato (TPS-Z) and corn (TPS-K) starch, the compatibilizer as well as PLA/TPS blends of 40 or 50 wt.% of starch was performed in a co-rotating twin-screw extruder. The structure of the obtained materials was evaluated by means of SEM (Figs. 1, 3) and FT-IR (Fig. 2) analysis. The dynamic (DMTA) as well as static mechanical (tensile and flexural) properties (Figs. 4-8, Tables 1-5) and also the biodegradability in the soil burial test (Table 6) were determined. The blends with the compatibilizer were characterized by improved tensile, flexural and impact resistance properties as compared to the composites without compatibilizer. This indicates, most probably, the occurrence of intensive interphase interactions between the hydrogen bonds of the anhydride groups of the compatibilizer and the hydroxy groups of the starch during the reactive extrusion process. The rate of biodegradation of the blends decreases with an increase in the content of compatibilizer.